The power of art in vulnerable contexts: impact and lived meanings of a community art intervention with adolescents in Bogotá (Colombia) - García García, Javier (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2026)
This article analyzes the impact of a community art intervention project developed at the Children and Youth Center for Community Development (CINJUDESCO) in Bogotá, Colombia, aimed at socially vulnerable adolescents. The initiative, promoted by the Granjas de San Pablo Neighborhood Association, integrates various artistic practices—literary rap, urban dance, freestyle soccer, and muralism—conceived not only as recreational activities but also as strategies for comprehensive support for the young people's life plans. The research, guided by the principles of evaluative research and based on a mixed-methods design of a parallel convergent type, used intentional non-probabilistic sampling. An evaluation questionnaire was administered to the center's director, a focus group was held with the management team and the trainers of the different artistic practices, and two in-depth interviews were conducted with participating adolescents. The results show that community-based artistic intervention has a positive impact on areas such as selfesteem, emotional regulation, and creativity, while promoting a sense of belonging and social cohesion in the environment, consolidating CINJUDESCO as a safe and transformative space for young people. Overall, it is concluded that art, understood as an educational and community tool, contributes to the development of resilience and peacebuilding in areas marked by exclusion and social inequality.
Keywords: Community intervention; art; social exclusion; youth; Colombia; community intervention